PRACTICAL IMPEDIMENTS TO CONVERGENCE OF U.S. GAAP AND IFRS - Gray, Krista; Spencer, Angela; Pumphrey, Lela (European Scientific Journal, ESJ, 2016)
The purpose of this paper is to examine one very important area in which convergence between accounting standards in the United States (U.S), which are referred to in the U.S. as generally accepted accounting principles (GAAP), and international financial reporting standards (IFRS) has not been achieved. We will try to explain the underlying reasons the U.S. has been unable to converge their accounting standards related to inventory valuation to international accounting standards and to examine the financial impact of a change in those standards on U.S-domiciled companies. The paper will examine the issues from the U.S. perspective. We will describe some of the differences between GAAP and IFRS on issues related to inventory. The disallowance of the LIFO cost assumption under IFRS, as well as the â€œlower of cost or net realizable valueâ€ rule used to determine the carrying value of inventory under IFRS rather than the â€œlower of cost or marketâ€ rule that is used under GAAP, are two major differences between the two sets of accounting standards related to inventory.